Carbon Nanotube Composites as Multifunctional Substrates for In Situ Actuation of Differentiation of Human Neural Stem Cells. Issue 11 (22nd April 2014) - Landers, John; Turner, Jeffrey T.; Heden, Greg; Carlson, Aaron L.; Bennett, Neal K.; Moghe, Prabhas V.; Neimark, Alexander V.
<x xml:space="preserve">Abstract</x> For the first time, single‐walled carbon nanotube–polymer composites are shown to enhance human neural stem cell (NSC) differentiation with electrical stimulation. The substrates are electrically conductive, mechanically robust, and highly biocompatible with human NSC cultures. The substrate's fibrous topography mimicking the extracellular matrix enhances neuronal lineage expression and electro‐conductivity provides means for controlled stimulation of neuronal maturation. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>